Bare Soil Carbon Dioxide Fluxes with Time and Depth Determined by High‐Resolution Gradient‐Based Measurements and Surface Chambers. Issue 4 (10th July 2015) - Xiao, X.; Kuang, X.; Sauer, T.J.; Heitman, J.L.; Horton, R.
Abstract : Soil CO2 production rates and fluxes vary with time and depth. The shallow near‐surface soil layer is important for myriad soil processes, yet knowledge of dynamic CO2 concentrations and fluxes in this complex zone is limited. We used a concentration gradient method (CGM) to determine CO2 production and effluxes with depth in shallow layers of a bare soil. The CO2 concentration was continuously measured at 13 depths in the 0‐ to 200‐mm soil layer. For an 11‐d period, 2% of the soil CO2 was produced below a depth of 175 mm, 8% was produced in the 50‐ to 175‐mm soil layer, and 90% was produced in the 0‐ to 50‐mm soil layer. Soil CO2 concentration showed similar diurnal patterns with temperature in deeper soil layers and out‐of‐phase diurnal patterns in surface soil layers. Soil CO2 flux from most of the soil layers can be described by an exponential function of soil temperature, with temperature sensitivity ( Q 10 ) ranging from 1.40 to 2.00 (1.62 ± 0.17). The temperature‐normalized CO2 fluxes are related to soil water content with a positive linear relationship in surface soil layers and a negative relationship in deep soil layers. The CO2 fluxes from CGM and chamber methods had good agreement at multiple time scales, which showed that the CGM method was able to estimate near‐surface soil CO2 fluxes and production. The contrasting patterns between surface and deep layers of soil CO2 concentration and fluxes suggest the necessity of intensive CO2 concentration measurements in the surface soil layer for accurate determination of soil‐atmosphere CO2 flux when using the CGM.